2018
DOI: 10.1007/s00408-018-0161-3
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Navigation Bronchoscopy: Where Are We Now? Five Years of a Single-Center Experience

Abstract: ENB is a safe procedure with a similar diagnostic yield in the real-life and research setting. Bronchus sign is an important factor in determining the diagnostic yield. ENB efficacy can be maximized by expertise and by a careful selection of each case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 35 publications
3
18
3
Order By: Relevance
“…Several studies investigating ENB's efficacy in diagnosing peripheral pulmonary nodules have reported variable diagnostic yields ranging from 69%-82.5%. 13,17 Although the diagnosis rate in this study was lower than that in previous studies, there are several considerations when interpreting these results. First, the type of sedation could affect ENB performance.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…Several studies investigating ENB's efficacy in diagnosing peripheral pulmonary nodules have reported variable diagnostic yields ranging from 69%-82.5%. 13,17 Although the diagnosis rate in this study was lower than that in previous studies, there are several considerations when interpreting these results. First, the type of sedation could affect ENB performance.…”
Section: Discussioncontrasting
confidence: 71%
“…The current study identified nodule size as an important factor associated with diagnostic yield. In previous investigations, the bronchus sign was also reported as a significant variable affecting the diagnostic yield 13,23 . This trend was observed in the univariate analysis but was irrelevant in the multivariate analysis in this study.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“… 9 Use of needle aspiration in only 16% of AQuIRE subjects may have contributed to the overall low rate of ENB-aided diagnostic yield in that study. 34 The choice to put the aspirating needle in the restricted group may be questioned by those who consider this tool standard-of-care. However, multiple published papers have reported low use of the aspirating needle, even in expert centers.…”
Section: Discussionmentioning
confidence: 99%
“…At our center, we did not use transbronchial needle aspiration (TBNA). In a recent retrospective study by Patrucco et al, TBNA was used in combination with ROSE, prior to transbronchial forceps biopsies and bronchoalveolar lavage. Procedures were performed during general anesthesia.…”
Section: Discussionmentioning
confidence: 99%